A potential new mechanism for pregnancy loss: considering the role of LINE-1 retrotransposons in early spontaneous miscarriage - Chao Lou; John L. Goodier; Rong Qiang (BMC, 2020)
Abstract LINE1 retrotransposons are mobile DNA elements that copy and paste themselves into new sites in the genome. To ensure their evolutionary success, heritable new LINE-1 insertions accumulate in cells that can transmit genetic information to the next generation (i.e., germ cells and embryonic stem cells). It is our hypothesis that LINE1 retrotransposons, insertional mutagens that affect expression of genes, may be causal agents of early miscarriage in humans. The cell has evolved various defenses restricting retrotransposition-caused mutation, but these are occasionally relaxed in certain somatic cell types, including those of the early embryo. We predict that reduced suppression of L1s in germ cells or early-stage embryos may lead to excessive genome mutation by retrotransposon insertion, or to the induction of an inflammatory response or apoptosis due to increased expression of L1-derived nucleic acids and proteins, and so disrupt gene function important for embryogenesis. If correct, a novel threat to normal human development is revealed, and reverse transcriptase therapy could be one future strategy for controlling this cause of embryonic damage in patients with recurrent miscarriages.